Pengaruh Seni Melipat Kertas dalam Meningkatkan Motorik Halus Anak Usia 5-6 Tahun di TK Insan Cemerlang Kota Makassar - Nunung Amriani; Musfira Musfira; Sri Suflianti Romba (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2025)
This study aims to test and find out the influence of the art of folding paper in improving Fine motor skills in early childhood, specifically for children aged 5 to 6 years, were studied at Insan Cemerlang Kindergarten in Makassar City. This research is quantitative and uses an experimental approach with a one-group pretest-posttest design. The study involved 17 children in the B1 group. Data was collected using test performance, observation, documentation, and children's checklist sheets based on the indicators of child development outlined in Minister of Education and Culture Regulation No. 17 of 2023. The data was analyzed using a non-parametric test called the Wilcoxon Signed Rank Test. The results showed that the pre-test score was 12.7, which increased to 17.1 after the children were given lessons in the art of folding paper, or origami. The Wilcoxon Signed Rank Test analysis produced a Z value of 3.630 with an Asymp.Sig (2-tailed) significance of 0.000. Since this significance is less than 0.05, the null hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted. This means there was a significant difference between the pre-test and post-test results. Therefore, it can be concluded that the activity of folding paper has a significant effect on improving fine motor skills in children aged 5 to 6 years.in early childhood in Insan Cemerlang Kindergarten in Makassar City.